Exploring the emotionally intelligent leadership of interfaith champions on campus. Issue 173 (29th July 2021) - Morin, Shauna M.; Durako Fisher, Lori E.; Singer, Kevin; Mayhew, Matthew J.; Rockenbach, Alyssa N.
Abstract: Worldview is often neglected as a dimension of holistic student learning and development in college, yet certain higher education practitioners are deeply committed to supporting students with diverse religious, spiritual, and secular identities. This article explores common characteristics among these "interfaith champions" and how their own worldview identities inform their commitment to advancing interfaith equity.